FAKTOR- FAKTOR YANG MEMENGARUHI BIDAN DALAM PEMBERIAN IMUNISASI HEPATITIS B PADA BAYI BARU LAHIR DI WILAYAH KERJA PUSKESMAS PANCUR BATU TAHUN 2015 - Rani Gartika Silalahi (Elisabeth Health Jurnal, 2016)
Hepatitis B is a liver disease caused by hepatitis B virus (VHB), a family member of Hepadnavirus that can cause chronic liver inflammation and may progress to liver cirrhosis. The prevalence of hepatitis B in Indonesia is still high due to transmission of hepatitis B disease from mother to childbirth. Goals : The purpose of this research is to know the factors influencing the midwife in giving Hepatitis B immunization to newborn in Pancur Batu Puskesmas Working Area. Methods : The type of research is survey with cross sectional data measurement method. The population is all mothers in the working area of Pancur Batu Community Health Center September 2015 assisted by 102 midwives, the entire population is sampled. Data analysis was done by univariate test, Chi Square and multiple logistic regression. Result : The results showed that motivation (p = 0.046, 95% CI 1.016-5,882), ability (p = 0,019, 95% CI 1,195-7,034) and midwife perception (p = 0,044; 95% CI 1,025-5,949) influence immunization Hepatitis B. The most influential variable is the ability with the value Exp B = 2.899 means that midwives who have good ability have an opportunity to provide hepatitis B immunization 2,899 times greater than the midwife with poor ability. The low coverage of immunization is due to approximately 64.7% of mothers saying the midwife did not explain to the mother that all newborns should be given this hepatitis B immunization, 59.2% of mothers said they did not get an explanation from the midwife about the benefits of hepatitis B immunization in infants, and 59.8% of mothers said they did not know that the first hepatitis B immunization given to infants should not pass from seven days after the baby was born so they thought hepatitis B immunization could be given when the baby was more than 1 month old. Conclution : It is advisable to Pancur Batu Puskesmas to further increase the coverage of hepatitis B immunization by increasing the role of mothers to bring their children immunization, and conduct training for all health workers. Give awards for midwives to motivate themselves more in carrying out their duties.